Agricultural transformation, technology adoption and inclusion of small farmers: The case of dairy in East Africa - Liz Ignowski; Bart Minten (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2021)
Based on unique primary surveys, we study dairy transformation processes in East Africa, specifically in Ethiopia and Uganda. Evidence on transformation and differential paths followed in doing so in these countries is often limited due to a lack of data. We note significant changes in the dairy sector over the last decade - with more adoption of cross-bred cows and higher milk yields - seemingly driven by rapid changes in local demand (Ethiopia and Uganda) and export markets (Uganda). However, while small farmers were included in that transformation in Uganda, they were not in Ethiopia. This was seemingly driven by better and cheaper accessibility for cross-bred cows that small farmers can better bear in Uganda.
Keywords: 330; Milchviehhaltung; Milchverarbeitung; Kleinbauern; Technischer Fortschritt; Agrartechnik; Landwirtschaftliche Entwicklung; Äthiopien; Uganda